Differential Effects of Single-Dose Escitalopram on Cognitive and Affective Interference during Stroop Task - Rahm, Christoffer G. (Frontiers in Psychiatry, 2014)
Background and objective: Our aim was to study the regulatory role of serotonin (5-HT) on two key nodes in the cognitive control networks - the anterior cingulate cortex (ACC) and the dorsolateral prefrontal cortex (DLPFC). We hypothesized that increasing the levels of 5-HT would preferentially modulate the activity in ACC during cognitive control during interference by negative affects compared to cognitive control during interference by a superimposed cognitive task. Methods: We performed a functional magnetic resonance imaging investigation on 11 healthy individuals, comparing the effects of the selective 5-HT reuptake inhibitor escitalopram on brain oxygenation level dependent signals in the ACC and the DLPFC using affective and cognitive counting Stroop paradigms (aStroop and cStroop). Results: Escitalopram significantly decreased the activity in rostral ACC during aStroop compared to cStroop (p< 0.05). In the absence of escitalopram, both aStroop and cStroop significantly activated ACC and DLPFC (Z≥2.3, p< 0.05). Conclusion: We conclude that escitalopram in a region and task specific manner modified the cognitive control networks and preferentially decreased activity induced by affective interference in the ACC.